THE PREVENTIVE MODEL FOR CHRONIC KIDNEY DISEASE IN COASTAL AREA ABELI HEALTH CENTRE IN KENDARI CITY: Preventive model of CKD - Tasnim Tasnim; Sunarsih Sunarsih; Timbul Supodo (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: Chronic kidney failure is an iceberg phenomenon whose cases are not known with certainty in the coastal community in the Abeli Health Center area, Kendari City. However, the visible risk factors are the high prevalence of hypertension and diabetes. Therefore, the development of a prevention strategy is urgently needed and this study aims to formulate a prevention model for chronic kidney failure in the coastal area of Kendari City. Methods: This study used a qualitative method with a case study design in 3 sub-districts in the coastal area of the Abeli Health Center, Kendari City. The study was conducted in May – June 2023. There were 15 informants who were interviewed in depth and most of them were women. The results of the interviews were transcribed verbatim and analyzed using theme analysis techniques. Visualization analysis and project map are used to formulate a community prevention model for chronic kidney disease. Results: The model of prevention efforts carried out by the community in the coastal area of the Abeli Health Center for the incidence of chronic kidney disease includes primary and secondary prevention. Primary prevention efforts include controlling food, checking health regularly, getting enough and regular rest, and doing enough physical activity. While the secondary prevention efforts are adequate and regular rest, stopping smoking, walking in the morning, doing activities at home. Conclusion: The results of this study are important to be followed up by the person in charge of the Abeli Health Center and the Southeast Sulawesi Provincial Health Office and the City of Kendari by developing policies that support strengthening community prevention efforts against chronic kidney disease in the Kendari City area.